The Global Cosmetic Industry: Regulatory Challenges and Innovations for Ensuring Safety and Compliance - Monika1*; Pragi1; Kumar, Varun; Jyoti2; Sarswa, Anish; Shrikant4; Malik, Gaurav; Kumari, Shabnam (Current Cosmetic Science, 2025)
The cosmetics industry is a dynamic, ever-expanding worldwide enterprise. The need for premium goods has led to the exponential rise of the beauty and cosmetics business in recent years. Governments worldwide are enforcing rules to ensure the safety and effectiveness of cosmetic products in response to the rapidly evolving sector. The global cosmetics industry is experiencing a surge in growth, driven by a growing emphasis on wellness and self-care, despite a minor setback during the COVID-19 pandemic. Global regulation of cosmetic products ensures efficacy and safety, but differing policies across nations can impact industry competitiveness and profitability. The global industry faces challenges due to differing regulatory frameworks across markets, which are not harmonized, restricting innovation and market growth. These differences also affect international trade and hinder the role of regulatory authorities. The European Union (EU's) cosmetic regulatory framework provided by Regulation (EC) No. 1223/2009, ensures uniformity across member states and adapts to technical progress. This Regulation, which took the place of the earlier, 1976- adopted Directive 76/768/EC, was an attempt to bring regulations in all EU member states into compliance while also keeping up with much-needed technological advancements. Globally regulatory agencies have their own regulations to assure the safety of cosmetics. The EU and the United States of America (USA) account for the majority of the cosmetic market. The regulations in these regions serve as a model for the developing globe. The article emphasizes the need for harmonization in cosmetic rules across countries, focusing on safety, stability, and labeling.
Keywords: ingredient safety